EVALUASI INTERNAL CONTROL BERBASIS COSO INTEGRATED FRAMEWORK UNTUK MENCEGAH FRAUD PADA SMA MUHAMMADIYAH 2 SURABAYA - Bagasrana Putra Fadhillah; Bonnie Soeherman (CALYPTRA, 2018)
SMA Muhammadiyah 2 Surabaya is one of the Islamic school in Surabaya and became the object of this research and school is example of not for profit organization. The Internal Control of this school is already good but it’s not considering the importance of fraud risk, so SMA Muhammadiyah 2 Surabaya can’t detect fraud. This research is intended to design a ideal internal control to prevent fraud to happen in SMA Muhammadiyah 2 Surabaya. This research use interview and observation method to collect data related to SMA Muhammadiyah 2 Surabaya internal control. The result of this research is the internal control of SMA Muhammadiyah 2 Surabaya can detect fraud if there’s a control about fraud from the beginning.